Interview: Raised in Pimp City: Urban insights on traffickers, trafficking, and the counter-trafficking industry - King, Armand; Gerasimov, Borislav; McAdam, Marika (Anti-Trafficking Review, 2022)
Armand King was involved in human trafficking for over a decade. The journal Editor, Borislav Gerasimov, and the Special Issue Guest Editor, Marika McAdam, conducted this interview with him to better understand his motivations and experiences during this period of his life as well as his views on counter-trafficking.